Adaptivity of network communities as a factor of the teacher’s successful professional development for the protection of the long life - Ramazanov, R.G. (Vestnik Rossiĭskogo universiteta druzhby narodov. Serii͡a︡ Informatizat͡s︡ii͡a︡ obrazovanii͡a, 2018)
In modern conditions, increasing the share of distance technologies, the role of network communities in the system of raising the qualifications of pedagogues becomes very significant. The processes of globalization, involving the mutual integration of cultures, the strengthening of interrelations between states and their individual structures, are often realized through internal informatization of the individual components of the system. This article presents the results of studies related to the development of the system of advanced training in modern conditions, the main components of the principles of lifelong learning. The basic properties and advantages of using adaptive network communities in the professional development of teachers are presented. The provisions on continuous education proposed in the article may have significance for the development of the theory of network interaction and use in practice in the construction of adaptive systems. The main ideas of continuous professional development implemented in the development model of an adaptive network community are presented. Continuous education helps the teacher to maintain and improve his professional level, to master various competencies throughout his pedagogical activity. In modern conditions adaptive network communities are the best tool for organizing lifelong learning.